2015
DOI: 10.1097/gox.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion and Synovial Cyst of the Temporomandibular Joint

Abstract: Summary:Ganglion and synovial cysts of the temporomandibular joint (TMJ) are rare. Although histopathological findings differ, clinical presentation is comparable. This study adds a case report of a ganglion of the TMJ to existing literature and a review of all available case reports on ganglion and synovial cysts of the TMJ. Including our own case report, we reviewed 49 cases of ganglion and synovial cysts of the TMJ. They occurred in a female:male ratio of 3:1, at an median age of 46 years (range, 11–64 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
(29 reference statements)
0
18
0
1
Order By: Relevance
“…On review of the literature, there are 29 reported cases of unilateral synovial cysts of the TMJ in the English literature 1–20. This is the second case report of bilateral TMJ synovial cysts.…”
Section: Discussionmentioning
confidence: 92%
“…On review of the literature, there are 29 reported cases of unilateral synovial cysts of the TMJ in the English literature 1–20. This is the second case report of bilateral TMJ synovial cysts.…”
Section: Discussionmentioning
confidence: 92%
“…TMJ ganglion within the external auditory canal is rare. The median age of patients is approximately 46, and TMJ cysts occur more commonly in the female gender with a ratio of 3 : 1 [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are thought to come about from myxoid degeneration of the connective tissue encompassing the joint capsule. Trauma and inflammation have been suggested to play a role [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment consists of complete surgical excision; recurrence rates are probably low because no recurrences have yet been reported. 17,37…”
Section: Tmj Ganglion and Synovial Cystmentioning
confidence: 99%